An overview of different seed production initiatives in Nepal - Paudel, MN; Pokhrel, S; Gadal, N; Ferrara, G Ortiz; KC, D; Joshi, P; Humagain, R (Agronomy Journal of Nepal, 2013)
Findings of study related to seed and seed initiatives in seven districts encompassing different classes of seed systems have been explained. Source seed produced by public and private institutions in Nepal is illustrated to make proper analogue as to how seed systems could be made practically functional. SWOT analysis of important seed systems is compared in issues pertaining to seed systems in Nepal. Information received from the seed related stakeholders has been analyzed to draw the inference covering different seed system initiatives in Nepal. On the basis of scientific evidences collected from concerned stakeholders from cross section of study districts on various issues of seed, recommendations have been proposed to make effective seed systems by amalgamation of available seed production initiatives under single funneled seed system that could be implemented to sustain food security and enhanced productivity of crops in general and major food crops in particular in Nepal. Agronomy Journal of Nepal (Agron JN) Vol. 3. 2013, Page 1-10 DOI: http://dx.doi.org/10.3126/ajn.v3i0.8981